2012
DOI: 10.1007/s10904-012-9672-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, Cytotoxic Activities and DNA-Binding Properties of a 1D Copper(II) Complex Bridged both by Oxamidate and Terephthalato Groups

Abstract: A new one-dimensional copper(II) polymer with formula of [Cu 2 (heae)(tpa)] n ÁnH 2 O, where heae 2-and tpa 2-stand for the dianions of N,N 0 -bis(N-hydroxyethylaminoethyl)oxamide and terephthalic acid, respectively, has been synthesized and characterized by elemental analysis, conductivity measurement, IR and electronic spectral studies, and single-crystal X-ray diffraction. The crystal structure consists of a one-dimensional copper(II) coordination polymeric chain constructed by the [Cu 2 (heae)] 2? cations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The same research group has reported the synthesis and structural characterization of a one-dimensional copper­(II) polymer [Cu 2 ( L 38 )­(tpa)] n · n H 2 O (Htpa = therephtalic acid). Also, this derivative was able to interact with HS-DNA via an intercalation mode and showed cytotoxicity against SMMC-7721 and A549 cells …”
Section: Copper Complexes As Anticancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same research group has reported the synthesis and structural characterization of a one-dimensional copper­(II) polymer [Cu 2 ( L 38 )­(tpa)] n · n H 2 O (Htpa = therephtalic acid). Also, this derivative was able to interact with HS-DNA via an intercalation mode and showed cytotoxicity against SMMC-7721 and A549 cells …”
Section: Copper Complexes As Anticancer Agentsmentioning
confidence: 99%
“…Also, this derivative was able to interact with HS-DNA via an intercalation mode and showed cytotoxicity against SMMC-7721 and A549 cells. 180 Bis-substituted copper(II) guanidine complexes [Cu-{PhCONHC(NHR)NPh}] have been structurally characterized (R = n-butyl, cyclohexyl), and eight new complexes have been tested for their cytotoxicity and antibacterial and antifungal activities. They were generally less active than the reference cisplatin drug, and only the aryl-substituted compounds diplayed a promising cytotoxic activity.…”
Section: O-donor Systemsmentioning
confidence: 99%